2020
DOI: 10.3390/molecules25133040
|View full text |Cite
|
Sign up to set email alerts
|

Neopapillarine, an Unusual Coumarino-Alkaloid from the Root Extract of Neocryptodiscus papillaris with Cytotoxic Activity on Renal Cancer Cells

Abstract: Several simple and prenylated coumarin derivatives were isolated from the dichloromethane extract of the root of Neocryptodiscus papillaris based on moderate cytotoxic activity of the extract in COLO205, KM12 and MCF7 cancer cells. While the major prenylated furanocoumarin derivatives and osthol isolated from the dichloromethane extract were responsible for the activity in the colon and breast cancer cell lines, the 4′-acylated osthol derivatives including a novel coumarino-alkaloid; neopapillarine) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The compound induced apoptosis in HeLa and SiHa cervical cancer cells by enhancing reactive oxygen species (ROS) generation while increasing the expression of cytochrome c and other apoptotic proteins. Palmatine and 6-methoxydihydroavicine isoquinoline alkaloids were isolated from Berberis cretica and Macleaya cordata , respectively [ 28 , 51 ]. Reports by Ma et al [ 28 ] and Zhang et al [ 27 ] suggest that 6-methoxydihydroavicine increased cellular ROS generation and interfered with mitochondria oxaloacetic acid metabolism during glycolysis in pancreatic and ovarian carcinoma cancer cells.…”
Section: Anticancer Alkaloids From Plantsmentioning
confidence: 99%
“…The compound induced apoptosis in HeLa and SiHa cervical cancer cells by enhancing reactive oxygen species (ROS) generation while increasing the expression of cytochrome c and other apoptotic proteins. Palmatine and 6-methoxydihydroavicine isoquinoline alkaloids were isolated from Berberis cretica and Macleaya cordata , respectively [ 28 , 51 ]. Reports by Ma et al [ 28 ] and Zhang et al [ 27 ] suggest that 6-methoxydihydroavicine increased cellular ROS generation and interfered with mitochondria oxaloacetic acid metabolism during glycolysis in pancreatic and ovarian carcinoma cancer cells.…”
Section: Anticancer Alkaloids From Plantsmentioning
confidence: 99%
“…Renal cell cancer is the most invasive malignant tumor of the urinary system and accounts for 2-3% of malignant tumors in adults (Lee et al, 2021). Tosun et al (2020) found that osthole exerted selective cytotoxic activities in a renal cell cancer cell line (A498, UO31).…”
Section: Urinary Systemmentioning
confidence: 99%
“…It has many active biological properties, such as antioxidant, antiinflammatory, antiviral, antibacterial, antifungal and anticancer activities [256][257][258]. To-sun et al [123] found that neopapillarine decreased cell growth in A498 and UO31 RCC cell lines, although mechanisms were not specified.…”
Section: Neopapillarinementioning
confidence: 99%